1995
DOI: 10.1002/chp.4750150105
|View full text |Cite
|
Sign up to set email alerts
|

Patient charts and physician office management decisions: Chart audit and chart stimulated recall

Abstract: Accurate assessment of clinical competence and performance in office practice is enhanced through a multi-tool approach. Two assessment tools that offer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 1 publication
0
25
0
Order By: Relevance
“…Moore et al25 found that CME subject matter was increasingly focused on seeking solutions to patient care problems. Jennett et al26 sought to obtain an accurate assessment of clinical competence and performance in office practice through a multi-tool approach. Results from that study confirmed that, in addition to physician competence, there are other factors that are significant to consider when analyzing management approaches, identifying areas for learning and designing CME interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Moore et al25 found that CME subject matter was increasingly focused on seeking solutions to patient care problems. Jennett et al26 sought to obtain an accurate assessment of clinical competence and performance in office practice through a multi-tool approach. Results from that study confirmed that, in addition to physician competence, there are other factors that are significant to consider when analyzing management approaches, identifying areas for learning and designing CME interventions.…”
Section: Introductionmentioning
confidence: 99%
“…This method was shown to have good face and content validity (Jennett 1995). In addition, it has been demonstrated that (with sufficient sampling) good levels of reliability (Norman 1993) and validity with assessor training (Solomon 1990) can be achieved.…”
Section: Origins Of Case-based Discussionmentioning
confidence: 96%
“…Jennett et al (1995) used both chart audit and CSR to assess the clinical competence of 20 practicing family physicians. Chart stimulated recall was found to expound on a broader range of information that could be used to assess physician's diagnostic, investigative, and treatment skills and the clinical reasoning behind those skills.…”
Section: Discussionmentioning
confidence: 99%